Impact of bioconvection on the free stream flow of a pseudoplastic nanofluid past a rotating cone. Issue 5 (27th March 2022) - Puneeth, Venkatesh; Sarpabhushana, Manjunatha; Anwar, Muhammad S.; Aly, Emad H.; Gireesha, Bijjanal Jayanna
Abstract: In the current work, the repercussions of Brownian motion and thermophoresis on the three‐dimensional free stream flow of tangent hyperbolic (pseudoplastic) nanofluid past a rotating cone are explored. The tangent hyperbolic model expresses the characteristics of a shear‐thinning nanofluid. Furthermore, oxytactic microorganisms were used as mixers to actively stabilize the nanoparticles. The movement of these microorganisms within the nanofluid gives rise to a major phenomenon termed bioconvection. The flow of nanofluid past a rotating cone finds applications in the field of nuclear reactors, biomedical applications, solar power collectors, steam generators, and so on. The mathematical model is designed using Buongiorno's model that describes the two major slip mechanisms experienced by the nanoparticles moving within a fluid namely thermophoretic force and Brownian motion. The model thus formed is nondimensionalized using the apt similarity transformation. The resulting system is solved by the RKF ‐ 45 $RKF - 45$ technique by adapting the shooting method. The velocity, temperature, concentration, and motile density profiles are graphically interpreted for different flow parameters involved in the study. It was observed that thermophoresis reduces concentration and enhances the temperature whereas Brownian motion enhanced both temperature and concentration profiles. Also, the increase in the mixed convection parameter effectively decreased the temperature of the nanofluid.